EVALUATION OF APPROXIMATED AND EXACT MULTIVARIATE TESTS FOR MEAN VECTORS: A DATA SIMULATION STUDY - LACERDA, Maurício Silva; NASCIMENTO, Jhennifer dos Santos; BARBOSA, Eduardo Campana; MANULI, Rômulo César; NASCIMENTO, Moysés; NASCIMENTO, Ana Carolina Campana; EMILIANO, Paulo Cesar (Brazilian Journal of Biometrics, 2022)
The present study aimed to evaluate, through data simulation, the multivariate statistical tests Likelihood ratio test (LRT) and Hotelling’s T2 test for mean vectors regarding the type I error rate and the power of test. The scenarios were designed to analyze test performance under the influence of p−variate normality, correlation, and homogeneity of variance, as well as number of variables and sample size. Our results show that the type I error rate was not affected by the violation of the assumptions of independence and homogeneity of variances, due to the presence of p−variate normality, differently from the power of test. In data simulation of p−variate distribution with heavier tails than usual (Student−t with 1 degree of freedom), the Hotelling’s T2 showed to be conservative, while the LRT showed better results, especially for small sample sizes.